2009
DOI: 10.1158/0008-5472.can-08-4689
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA Synthetase VL3 Knockdown Inhibits Human Glioma Cell Proliferation and Tumorigenicity

Abstract: The contribution of lipid metabolic pathways to malignancy is poorly understood. Expression of the fatty acyl-CoA synthetase ACSVL3 was found to be markedly elevated in clinical malignant glioma specimens but nearly undetectable in normal glia. ACSVL3 levels correlated with the malignant behavior of human glioma cell lines and glioma cells propagated as xenografts. ACSVL3 expression was induced by the activation of oncogenic receptor tyrosine kinases (RTK) c-Met and epidermal growth factor receptor. Inhibiting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 44 publications
(61 reference statements)
8
59
0
Order By: Relevance
“…These siRNAs have previously been shown to inhibit ACSVL3 expression in adherent human GBM cells [14]. Quantitative RT-PCR (qRT-PCR) revealed that ACSVL3 si3 and ACSVL3 si4 inhibited ACSVL3 mRNA levels in GBM neurosphere cells by ∼60% and ∼55%, respectively (Figure 2A, P  < 0.01).…”
Section: Resultsmentioning
confidence: 86%
“…These siRNAs have previously been shown to inhibit ACSVL3 expression in adherent human GBM cells [14]. Quantitative RT-PCR (qRT-PCR) revealed that ACSVL3 si3 and ACSVL3 si4 inhibited ACSVL3 mRNA levels in GBM neurosphere cells by ∼60% and ∼55%, respectively (Figure 2A, P  < 0.01).…”
Section: Resultsmentioning
confidence: 86%
“…Theoretically, the true precursor for IM TG synthesis is fatty acyl-CoA ( 18 ). When fatty acids enter the intracellular pool, the fi rst step is to be converted to metabolically active fatty acyl-CoA, catalyzed by fatty acyl-CoA synthase and synthetase ( 19,20 ). Our recent results from a complementary experiment demonstrated that the transport of fatty acids into the IM compartment and their subsequent conversion to fatty acyl-CoA and fatty acyl-carnitine occurred very fast, with the peak enrichment within 2 min after a bolus palmitate tracer injection (unpublished data).…”
Section: Discussionmentioning
confidence: 84%
“…It is also present on the mitochondria of cultured neural cell lines and can activate both long-chain and very long-chain FAs (153). The expression of Fatp3 is high in lung tumors (154) and in malignant glioma compared to normal glia (157). Knockdown by RNAi in human glioma and lung cell lines diminishes long-chain FA activation and inhibits anchorage-dependent and independent cell growth and the growth of xenografts via diminished Akt phosphorylation (154, 157).…”
Section: The Fatp/acsvl/scl27a Familymentioning
confidence: 99%